AI Integration Within the Architectural Design Process and Management, and its Influence on Project Agility: A Literature Review, Bibliometric, and Survey Analysis - MANSOUR, ABDULHAK N (2024)
The integration of artificial intelligence (AI) in the architectural design process and project management will have a transformational effect on the industry, offering new opportunities to enhance creativity, productivity, and project agility. This study investigates the impact of AI integration within architectural design and management processes, and its influence on project agility and outcomes, focusing on key mediating variables such as increased architectural creativity and project management predictivity and automation, while considering moderating factors like the firm size and project complexity. Employing a mixed-methods approach, the research combines a comprehensive literature review, a survey of industry professionals, and bibliometric analysis using the VOSviewer software on SCOPUS database results. The literature review identifies existing trends, theories, and challenges in AI adoption, while the survey gathers quantitative insights on professionals’ experiences with AI tools. The bibliometric analysis visualises research trends and influential studies, offering a quantitative perspective on the field. The findings reveal that AI integration significantly enhances project agility and outcomes, primarily through increased design creativity and automation in project management. However, its effectiveness is influenced by organisational factors like the firm size, project complexity, and budget. This study provides insights for architects, project managers, and researchers, highlighting AI’s potential to reshape architectural practices and project management strategies.